Exceptional adsorption-induced cluster and network deformation in the flexible metal-organic framework DUT-8(Ni) observed by in situ X-ray diffraction and EXAFS - Bon, Volodymyr; Klein, Nicole; Senkovska, Irena; Heerwig, Andreas; Getzschmann, Juergen; Wallacher, Dirk; Zizak, Ivo; Brzhezinskaya, Maria; Mueller, Uwe; Kaskel, Stefan (Physical Chemistry Chemical Physics, 2015)
The "gate opening" mechanism in the highly flexible MOF Ni2(2,6-ndc)2dabco (DUT-8(Ni), DUT = Dresden University of Technology) with unprecedented unit cell volume change was elucidated in detail using combined single crystal X-ray diffraction, in situ XRD and EXAFS techniques. The analysis of the crystal structures of closed pore (cp) and large pore (lp) phases reveals a drastic and unique unit cell volume expansion of up to 254%, caused by adsorption of gases, surpassing other gas-pressure switchable MOFs significantly. To a certain extent, the structural deformation is specific for the guest molecule triggering the transformation due to subtle differences in adsorption enthalpy, shape, and kinetic diameter of the guest. Combined adsorption and powder diffraction experiments using nitrogen (77 K), carbon dioxide (195 K), and n-butane (272.5 K) as a probe molecules reveal a one-step structural transformation from cp to lp. In contrast, adsorption of ethane (185 K) or ethylene (169 K) results in a two-step transformation with the formation of intermediate phases. In situ EXAFS during nitrogen adsorption was used for the first time to monitor the local coordination geometry of the metal atoms during the structural transformation in flexible MOFs revealing a unique local deformation of the nickel-based paddle-wheel node.
CRIS-Team Scopus Importer:2023-03-20